Greenhouse Gases Selected Case Studies - Manning, Andrew J. (IntechOpen, 2016)
Greenhouse Gases - Selected Case Studies, is a book which covers a range of topics. The long term effective management of the natural environment, requires a detailed understanding of greenhouse gases. This has both environmental and economic implications, especially where there is any anthropogenic involvement. Numerical models are often the tool and framework used for predicting the effects, both in the long-term and short-term, of greenhouse gases. However, the relevant atmospheric processes can vary quite considerably depending upon the spatial and temporal scales under consideration. For this reason for the past few decades, scientists, engineers, meteorologists and mathematicians have all been continuing to conduct research into the many aspects which influence greenhouse gases. These issues range from: industrial science, agricultural research, carbon dioxide and other emissions. This book reports the findings from recent research in greenhouse gases, primarily in the the form of case studies, particularly from an interdisciplinary perspective. The research was carried out by researchers who specialise in areas such as: energy production, emissions from livestock, chemical industry, and metallurgical process technology.